INDEPENDENSI DEWAN, FREKUENSI RAPAT, KEPEMILIKAN INSTITUSIONAL DAN KINERJA PERUSAHAAN: BOARD INDEPENDENCE, BOARD MEETING FREQUENCY, INSTITUTIONAL OWNERSHIP AND COMPANY PERFORMANCE - Nela Safelia; Yuliusman Yuliusman (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The performance index of companies in the infrastructure, utilities, and transportation sectors experienced a decline of 12% at the end of 2020. This fact triggered this research to find out and analyze how company performance is influenced by board independence, frequency of meetings, and institutional ownership. The research sample are 80 companies in the infrastructure, utility, and transportation sectors listed on the Indonesia Stock Exchange during 2018-2020, which were obtained by purposive sampling. The data analysis technique is multiple linear regression analysis. The results showed that partially the frequency of meetings and institutional ownership had an effect on company performance, while the board independence variable had no effect.